In depth: Groundwater: A remedy for water crises? - Mila Ibrahimova (The UNESCO Courier, 2022)
Growing use along with the increased pressure on surface water resources is making global water crises unavoidable – unless we tap into the full potential of Earth’s groundwater resources, which offer an enormous supply of freshwater.